Understanding through structure: The challenges of information and navigation architecture in cybercartography - Parush, A. (Avi); Pulsifer, P. (Peter); Philp, K. (Karen); Dunn, G. (Greg) (Cartographica: The International Journal for Geographic Information and Geovisualization, 2006)
The information-rich environments suggested by the concept of cybercartography present new challenges to the design and display of interactive geographically oriented information. These new challenges revolve around two basic issues: information architecture and information navigation models. A variety of information architectures are discussed in this article, along with an analysis of topologies such as the hierarchy (tree), linear sequence, matrix (grid), web-like, or hybrid. A three-tier information architecture model is proposed that varies in information granularity. The high-granularity level includes information units such as maps, articles, images, animations, video clips, and data graphs. The medium-granularity level includes integrated functional information units that are topical, task oriented, audience specific, or a hybrid. At such a level of information units, maps are no longer a stand-alone element. Finally, the low-granularity level includes top-level information architecture linking the various functional units. The advantage of these three granularity levels is that they enable an adaptable information architecture that can accommodate the addition of new content composed of the basic elements. While the way users navigate such an information architecture can be prescribed by the information structure, we demonstrate how navigation schemes can be independent of the information architecture and offer the user a greater diversity of interaction.